The "tambla" (Humuya) gomphothere (Honduras): the first report of fossil vertebrates in Central America - Lucas, Spencer G.; Bonta, Mark; Rogers, Robert; Alvarado, Guillermo E. (Revista geológica de América central, 2011)
.